Identification of immune-related genes in gill cells of Japanese eels (Anguilla japonica) in adaptation to water salinity changes. Issue 73 (February 2018) - Gu, Jie; Dai, Shuya; Liu, Haitao; Cao, Quanquan; Yin, Shaowu; Lai, Keng Po; Tse, William Ka Fai; Wong, Chris Kong Chu; Shi, Haifeng
Abstract: The changes in ambient salinity influence ion and water homeostasis, hormones secretion, and immune response in fish gills. The physiological functions of hormones and ion transporters in the regulation of gill-osmoregulation have been widely studied, however the modulation of immune response under salinity changes is not determined. Using transcriptome sequencing, we obtained a comprehensive profile of osmo-responsive genes in gill cells of Japanese eel ( Anguilla japonica ). Herein, we applied bioinformatics analysis to identify the immune-related genes that were significantly higher expressed in gill pavement cells (PVCs) and mitochondrial-rich cells (MRCs) in freshwater (FW) than seawater (SW) adapted fish. We validated the data using the real-time qPCR, which showed a high correlation between the RNA-seq and real-time qPCR data. In addition, the immunohistochemistry results confirmed the changes of the expression of selected immune-related genes, including C-reactive protein (CRP) in PVCs, toll-like receptor 2 (TLR2) in MRCs and interleukin-1 receptor type 2 (IL-1R2) in both PVCs and MRCs. Collectively our results demonstrated that those immune-related genes respond to salinity changes, and might trigger related special signaling pathways and network. This study provides new insights into the impacts of ambient salinity changes on adaptive immune response in fish gill cells. Highlights: We applied bioinformatics analysis to identify the differentially expressed immune-related genes in gill cells. We validated differentially expressed immune-related genes, including 20 in gill PVCs and 11 in gill MRCs. CRP in gill PVCs, TLR2 in MRCs and IL1R2 in both PVCs and MRCs were down-regulated in higher salinity condition. Immune-related genes in gill cells were involved in adaptive immune response of fish adaptation to water salinity changes.